Comparison of Chest-to-Back Skin-to-Skin Contact and Chest-to-Chest Skin-to-Skin Contact on the Risk of Oxygen Desaturation and Change in Heart Rate in Low Birth Weight and/or Premature Babies: A Randomized Controlled Clinical Trial - Sisay Gere; Yemane Berhane; Alemayehu Worku (International Journal of Pediatrics)
Chest-to-chest (CC) skin-to-skin contact (SSC) is a widely used method of SSC to prevent low birth weight (LBW) and/or premature babies with the risk of hypothermia. However, very recently, a study has also shown that the chest-to-back (CB) SSC is also useful for such a purpose. It is also evident that CC SSC enhances the cardiorespiratory performance of LBW and/or premature babies from the risk of cold stress. However, whether babies kept in CB SSC have the risk of clinically relevant decreases of oxygen saturation or critical changes of the baby heart rate comparing the two SSC methods has been studied hardly. Thus, we assessed the risk of oxygen desaturation and changes in babies’ heart rate among LBW and/or premature babies kept in CB SSC compared to the standard. In this study, we enrolled 46 LBW and/or premature babies born between 32 and 37 completed weeks of gestation. We used a parallel-group randomized controlled clinical trial. Peripheral arterial blood oxygen saturation (SpO2) and heart rate (HR) were measured using an OxiMaxN-600X Pulse Oximeter. We transformed these measurements into stability of the cardiorespiratory system in premature infant (SCRIP) scores. We applied a generalized estimating equation model to analyze the data. No statistically significant difference was observed between babies kept in CB SSC compared to babies kept in CC SSC in either blood oxygen saturation or heart rate (P>0.05). Thus, the CB SSC can be used as one possible way to care for LBW and preterm babies in the kangaroo mother care. We suggest more studies before scaling up the approach in routine care.